INTRADIALYTIC ORAL NUTRITIONAL SUPPLEMENTS AND SURVIVAL IN MAINTENANCE HEMODIALYSIS PATIENTS - Eduardo Lacson; Weiling Wang Jr; Barbara Zebrowski; Rebecca Wingard; Raymond Hakim (The Korean Society of Nephrology, 2012)
Use of intradialytic oral nutritional supplements (ONS) improve nutritional biomarkers but an association with survival has not been proven. We evaluated mortality, comparing patients with serum albumin ≤3.5 g/dL who received monitored ONS (at no patient cost) during chronic outpatient hemodialysis (HD) as part of a standardized national program in Fresenius Medical Care, North America facilities, with eligible patients who did not receive ONS (controls). Participation was promoted but not mandatory. Study enrolment covered Q4‐2009 and follow‐up was until 12/31/10. Patients who received ONS outside of the program or started during 2010 were excluded. Two protein bars and two liquid formulations of ONS options were offered, which were available until albumin was ≥ 4.0 g/dL. Crude mortality in the ONS group (N= 7,264) was 29.4% vs. 36.6% for controls (N= 13,853), p<0.001. Compared to controls, the unadjusted mortality hazard ratio for ONS was 0.70 (0.67, 0.74) and after adjustment for baseline case‐mix and 5 quality indicators was 0.68 (0.64, 0.71). Although limited by the observational design, these results indicate favorable survival associated with ONS use in malnourished chronic HD patients with albumin ≤3.5 g/dL.